(untitled) (Research, Society and Development, 2020)
Introduction: Anacardium occidentale, popularly known as cashew, is a plant native to Brazil and has been widely used by the population due to its medicinal properties. Objective: To carry out a bibliographic search to show the profile of the use of A. occidentale as a medicinal plant and to correlate this information with experimental research that shows the biological potentials of this plant. Methodology: This is a narrative-type literature review. The search for articles occurred in the Lilacs, Scielo and Periódicos Capes databases, using the terms: 1) Anacardium occidentale; 2) Cashew tree and 3) Biological Activities, using the Boolean operators “AND” and “OR”. Results: Of 40 studies analyzed, 17 were used to compose the results. It was evidenced the use of cashew by different populations for the treatment of inflammation, stroke, injuries, diarrhea, infections, headache, toothache, hangover, as an astringent, anticoagulant, anti-flu, antipyretic and healing. Among these indications, anti-inflammatory, healing, anti-diarrheal, anti-flu and antimicrobials stand out, due to the existence of experimental studies proving these different biological potentials. Extracts of fruits, leaves and stem, demonstrate anti-inflammatory potential. The bark extract has healing potential, due to the presence of phenolic compounds, which seem to favor tissue reconstruction, due to its healing, antibacterial effects and because it influences mediators involved in inflammation. Regarding the antidiarrheal potential, studies with stem bark extract and A. occidentale gum showed reduced gastrointestinal transit, increased water and electrolyte reabsorption and delayed onset of diarrhea. In addition, high amounts of flavonoids and moderate amounts of alkaloids and tannins were obtained. As for the anti-flu activity, a promising anti-influenza activity was observed, through the ability to inhibit the neuraminidase enzyme and inhibit viral replication in mice. Antimicrobial activity was verified in Gram-positive and negative bacteria and fungi, being associated with the presence of alkaloids and tannins. Conclusion: Thus, it is understood that the cashew tree has a range of therapeutic indications in popular use, among which stands out its potential in anti-inflammatory, scarring, anti-diarrheal, anti-flu and anti-microbial processes, however it is worth mentioning that more research is needed clarify the possible mechanisms involved.